PENGABDIAN MASYARAKAT DI RT 01 LK 04 KELURAHAN KELAPA TUJUH OLEH MAHASISWA UNIVERSITAS MUHAMMADIYAH KOTABUMI TAHUN 2020 - Fhela Vhantoria Ningrum (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2022)
Independent KKN (Real Work Lecture) is one of the compulsory courses for students of the Muhammadiyah Kotabumi University to devote themselves to the community. KNN is a form of activity where students serve the community for about 1 month, move and go down directly to overcome problems that exist in the community. The work programs that have been implemented are in the fields of education, al-Islam and Muhammadiyah and counseling and prevention of Covid19. The results of the activities of each field of the compulsory KKN work program are 1) helping students in online learning, 2) helping students in solving problems in online learning difficulties, 3) re-running the recitation of mothers, 4) implementing TPA for children children, 5) conveyed the dangers of the covid 19 virus, and 6) distributed health masks and provided washing hands in public places. Thus the independent KKN work program of the Muhammadiyah Kotabumi University in 2020/2021 has been going well